2012
DOI: 10.1248/cpb.c12-00526
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activities of 1α,4α,25- and 1α,4β,25-Trihydroxyvitamin D<sub>3</sub> and Their Metabolism by Human CYP24A1 and UDP-Glucuronosyltransferase

Abstract: A previous report has demonstrated the existence of a C4-hydroxylated vitamin D 2 metabolite in serum of rats treated with pharmacological doses of vitamin D 2 . However, the biological significance and metabolic fate of this metabolite have not been described. To explore its potential biological activities, we therefore syn- The authors declare no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…This is a totally different effect from that of the 4-OH group. 25) Although O2C3 was resistant to CYP24A1, its CYP3A4 metabolite 2 was further metabolized by CYP24A1, similar to 1. The k cat /K m value of hCYP24A1 for 2 was 60% of that for 1.…”
Section: Resultsmentioning
confidence: 99%
“…This is a totally different effect from that of the 4-OH group. 25) Although O2C3 was resistant to CYP24A1, its CYP3A4 metabolite 2 was further metabolized by CYP24A1, similar to 1. The k cat /K m value of hCYP24A1 for 2 was 60% of that for 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, the occurrence of the 4-hydroxylation of 1,25D 3 by CYP3A4 remains to be demonstrated and the biological significance of 4-hydroxymetabolites remains elusive. The only available biological data concern synthetic 1,4α,25D 3 and 1,4β,25D 3 ligands (Figure 1B) and the results of luciferase reporter assays in transfected human osteosarcoma cells indicate that both isomers are less active than 1,25D 3 [15,16]. Interestingly, significant differences in CYP24A1-induced 1,4,25D 3 metabolism have been observed between the two isomers, and only the 4α isomer has been shown to be glucuronidated by certain hepatic UGT(s) [16,17].…”
Section: Synthesis: General Informationmentioning
confidence: 99%
“…The only available biological data concern synthetic 1,4α,25D 3 and 1,4β,25D 3 ligands (Figure 1B) and the results of luciferase reporter assays in transfected human osteosarcoma cells indicate that both isomers are less active than 1,25D 3 [15,16]. Interestingly, significant differences in CYP24A1-induced 1,4,25D 3 metabolism have been observed between the two isomers, and only the 4α isomer has been shown to be glucuronidated by certain hepatic UGT(s) [16,17]. In addition, 4β,25D 3 has been shown to have greater metabolic stability and resistance to CYP24A1 than 4α,25D 3 [18].…”
Section: Synthesis: General Informationmentioning
confidence: 99%
“…We have demonstrated that the E. coli expression system is quite useful to investigate enzymatic properties of CYP24A1. Using this E. coli expression system, we have determined kinetic parameters of CYP24A1 in the metabolism of the native vitamin D and various vitamin D derivatives, and revealed their metabolic pathways [45][46][47][48][49][50][51][52][53][54][55][56][57][58]. CYP24A1 plays central roles in vitamin D metabolism and produces a wide variety of metabolites.…”
Section: Construction Of a Cyp24a1 Enzyme System Containing Adrenodoxin (Adx) And Nadph-adrenodoxin Reductase (Adr)mentioning
confidence: 99%